DM, Visualisasi, Manajemen Stres MANAJEMEN STRES LATIHAN VISUALISASI TERHADAP GULA DARAH PENDERITA DIABETES MELLITUS - Dwiharini Puspitaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2017)
Abstract Visualization exercise combined breath relaxation is an alternative to reducing the stress of diabetics. The objective of the study to identify the effect of visualization exercise on blood sugar of diabetes mellitus patients. The research design was quasy experiment. The respondents are 16 divided into intervention and control groups. The results study, both intervention and control group experienced a decrease in blood sugar after treatment. The independent t test results obtained ? = 0.810 (? > 0.05) showed no significant differences in the intervention group and control group. Provision of interventions for 1 month is possible not followed by changes in respondent behavior so it is not significant enough in reducing blood sugar. Keywords: Visualization exercise, blood sugar, Diabetes Mellitus